2010
DOI: 10.1080/03601231003799945
|View full text |Cite
|
Sign up to set email alerts
|

Microbial degradation of 4-monobrominated diphenyl ether in an aerobic sludge and the DGGE analysis of diversity

Abstract: Polybrominated diphenyl ethers (PBDEs) were applied as flame retardant additives in polymers for many plastic and electronic products. Due to their ubiquitous distribution in the environment, potential toxicity to human and tendency for bioaccumulation, PBDEs have raised public safety concern. In this study we examined the degradation of 4-monobrominated diphenyl ether (4-BDE) in aerobic sludge, as a model for PBDE biodegradation. Degradation of 4-BDE was observed in aerobic sludge. Co-metabolism with toluene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…Previous studies showed that aerobic bacteria play an important role in the biodegradation of halogenated compounds with less than five halogen atoms (Chang et al, 2013;Chen et al, 2010). Aerobic bacterium with the ability of debrominating deca-BDE was also isolated from sediment by Deng (Deng et al, 2011); while for the microbial degradation of higher halogenated compounds, it was proved by different researches that the compounds were dehalogenated under anaerobic conditions by various anaerobic bacteria (Bedard, 2003;Bedard et al, 2005;He et al, 2006;Tokarz et al, 2008;Yen et al, 2009).…”
Section: Dynamics Of Microbial Composition and Functionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies showed that aerobic bacteria play an important role in the biodegradation of halogenated compounds with less than five halogen atoms (Chang et al, 2013;Chen et al, 2010). Aerobic bacterium with the ability of debrominating deca-BDE was also isolated from sediment by Deng (Deng et al, 2011); while for the microbial degradation of higher halogenated compounds, it was proved by different researches that the compounds were dehalogenated under anaerobic conditions by various anaerobic bacteria (Bedard, 2003;Bedard et al, 2005;He et al, 2006;Tokarz et al, 2008;Yen et al, 2009).…”
Section: Dynamics Of Microbial Composition and Functionmentioning
confidence: 98%
“…Aerobic and anaerobic biodegradation of such compounds have been investigated extensively (Bedard, 2003;Chang et al, 2013;Chen et al, 2010;Cutter et al, 2001;Dabrowska and Rosinska, 2012;Deng et al, 2011;Fennell et al, 2004;Li et al, 2005;Payne et al, 2011Payne et al, , 2013Rayne et al, 2003;Shih et al, 2012). Aerobic microbial degradation is often possible only when halogenated compounds have a maximum of four-to-five halogen atoms, although an aerobic bacterium responsible for deca-BDE debromination was isolated from sediment (Deng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The three commercial formulations vary in their critical effects and effective doses-with the penta-BDEs appearing to cause adverse effects at comparably lower doses, and deca-BDE at higher doses (Darnerud 2003). Higher brominated PBDEs can be debrominated to lower brominated congeners in biota (Stapleton et al 2004;Roberts et al 2011;Stapleton et al 2006) or in the environment, by exposure to UV light (Soderstrom et al 2004) or by microbial degradation (Chen et al 2010). Numerous studies have identified a range of adverse effects in wildlife and humans after exposure to PBDEs (Darnerud 2003(Darnerud , 2008.…”
Section: Introductionmentioning
confidence: 98%
“…In our previous study, the mono-BDE is transformed to diphenyl ether in an aerobic culture from sewage sediment, indicating an anaerobic debromination reaction occurred. The enriched Clostridiales specie shown in the denatured gradient gel electrophoresis (DGGE) may responsible for such reaction [55].…”
Section: Anaerobic Reductive Dehalogenationmentioning
confidence: 99%